The West Dallas environmental health project: the importance of community health experiences related to air pollution - Favorite, Xiara; Cisneros, Janie; Kendrick, Alicia; O’Quinn, Misti; Mayo, Evelyn; Roberts, Caleb; Johnson, Natalie; Ma, Ping (Frontiers in Public Health, 2025)
Racial and ethnic minorities experience a disproportionate exposure to air pollutants, such as fine particulate matter (PM2.5) and nitrogen dioxide (NO2), due to historical racial zoning increasing in proximity to industrial facilities. PM2.5 is associated with several adverse health effects including cardiopulmonary diseases, lung cancer, and adverse birth outcomes. Hence, reducing pollution exposure in minority communities, i.e., environmental justice (EJ) communities, holds great promise for reducing disparities in associated health burdens and improving health equity. In Dallas, Texas, residents living in an EJ community known as the “Singleton Corridor,” formed an action group to spread awareness of local pollution risks. Academic and community partners initiated a pilot study using a community-based participatory research (CBPR) approach, wherein volunteers administered a household survey from July to December 2023. Additionally, neighborhood-level PM2.5 concentration data from low-cost sensors were publicly accessible from the University of Texas at Dallas’ SharedAirDFW network and the City of Dallas. A total of 86 households completed the community survey. The majority of survey respondents (60.5%) rated the air quality as low or very low. 83.7% of respondents reported that air pollution in their neighborhood had made them or their family members sick. More than 60% of participants reported they avoid exercising outdoors and opening their windows due to concern about air pollution. 31.4% of respondents reported a lifetime diagnosis of asthma, with 26.7% reporting current asthma. Air monitoring data indicated potential PM2.5 hotspots necessitating further inquiry. Overall, the findings from this study indicate significant community concerns about air pollution exposure and a high prevalence of asthma.